Flexural Behavior of Precast Hollow Core Slab Using PVC Pipe and Styrofoam with different Reinforcement. (2017) - Wariyatno, Nanang Gunawan; Haryanto, Yanuar; Sudibyo, Gathot Heri
Abstract: The total weight of the building is greatly influenced by the self-weight of the reinforced concrete. The hollow core slab is one of alternatives to reduce its self-weight. On the other hand, with advancements in the quality of materials, workmanship and new technologies, precast concrete has become popular in the construction industry. This study discusses the flexural behavior of precast hollow core slab with different type of reinforcements. The test specimens consist of a solid slab as a reference slab, a hollow core slab type 1 (using PVC pipe to create the cavities), and a hollow core slab type 2 (using styrofoam to create the cavities). The diameter of steel reinforcements used in this study are 10 mm plain and deformed bars, 12 mm plain bars, and 13 mm deformed bar. The slab thickness was 12 cm. The results showed that hollow core slab type 1 and type 2 can reduce the weight by 24% and 25% as compared to the solid slab. Flexural strength of hollow core slab type 2 is higher than the hollow core slab type 1. However, it is lower than the solid slab with all variations in reinforcement diameter. The value of flexural stiffness of the solid slab is greater than hollow concrete slab type 1 and type 2. Cracks that occur in solid slab are distinguished as flexural crack, while the cracks that occur in the hollow core slab type 1 and type 2 are shear cracks.